DESCRIPTION OF EARLY CHILDHOOD CARIES WITH CHRONOLOGICAL AGE OF DENTAL IN PRESCHOOL CHILDREN AT RSGM UNJANI - Rhabiah El Fithriyah; Henri Hartman; Farhan Yudistira (Fakultas Kedokteran Gigi Unjani, 2023)
Early Childhood Caries (ECC) is a chronic disease in children that is most common under 71 months and is a multifactorial disease that can be seen directly (Intra Oral) or by radiographs. This study aims to determine the picture of ECC at preschool age assessed through radiographs. This research method is a descriptive observational study with a cross-sectional approach. The number of research subjects was 39 from the radiological data of the RSGM UNJANI. Sampling was in accordance with the inclusion and exclusion criteria, consisting of radiographs aged 3-5 years. The study was conducted by assessing the level of tooth decay in children using radiographs. Data processing using SPSS with the univariate analysis aims to describe the chronological Age and Early Childhood Caries using frequency distribution and percentage. The results of this study indicate that children aged 3-5 years are susceptible to early caries. This study concludes that ECC occurs mainly in preschool children with severe categories. DOI : 10.54052/jhds.v2n3.p429-438